2006
DOI: 10.1111/j.1572-0241.2006.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bispectral Monitoring as an Adjunct to Nurse-Administered Propofol Sedation for Colonoscopy: A Randomized Controlled Trial

Abstract: BIS did not lead to reductions in mean propofol dose or recovery time when used as an adjunct to NAPS for colonoscopy, or when used as the primary target for sedation. No clinically important role for BIS monitoring as an adjunct to NAPS has yet been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 17 publications
5
47
0
3
Order By: Relevance
“…Bispectral (BIS) monitoring is now available for the assessment of the depth of sedation, and some studies on its use during endoscopic procedures for the purpose of reducing the dose of propofol have been reported (17)(18)(19). Unfortunately, no study could succeed in reduction of the dose of propofol, although satisfaction of anesthesiologists and patients was improved.…”
Section: Discussionmentioning
confidence: 99%
“…Bispectral (BIS) monitoring is now available for the assessment of the depth of sedation, and some studies on its use during endoscopic procedures for the purpose of reducing the dose of propofol have been reported (17)(18)(19). Unfortunately, no study could succeed in reduction of the dose of propofol, although satisfaction of anesthesiologists and patients was improved.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies of BIS or alternative EEG-based monitoring of sedation during endoscopy reported that these tools correlated well with the level of patient consciousness [32], and permitted more effective titration of propofol and faster recovery from sedation during endoscopy [33]. However, subsequent studies at our institution have questioned the utility of BIS monitoring during nurse-administered propofol sedation (NAPS) for outpatient colonoscopy [34,35]. The use of BIS monitoring for advanced endoscopic procedures such as EUS has not been studied to date.…”
Section: Introductionmentioning
confidence: 96%
“…Another pilot study described bispectral monitoring as part of a closed monitoring cycle for the continuous infusion of propofol in 16 patients sedated for colonoscopy [4]. However, in more recent studies, BIS monitoring was not found useful to titrate propofol sedation for colonoscopy [5,6]. In both trials, neither propofol dose reduction nor corresponding shorter recovery times were attained by using BIS monitoring.…”
Section: Eeg Monitoring With Bispectral Index Monitoringmentioning
confidence: 99%